PROSES SOSIALISASI LAKI-LAKI SUKA SEKS DENGAN LAKI-LAKI (LSL) PADA KALANGAN REMAJA DI KABUPATEN JEMBER - Rokhmah, Dewi; Nafikadini, Iken; Luthviatin, Novia; Istiaji, Erdi (IKESMA, 2012)
The Men who like Sex with Men (MSM) is a minority in heterosexual society.Â The Young MSM community always close their identity in the society becuse they need self actuality as homosexual in the heterosexuaal society. This will have an impact on their lack of information and knowledge about reproductive health. The purpose of this study was to analyze the process of socialization among young MSM and its effects on adolescent reproductive health, which includes socialization in the family, at school (college), in the MSM community and the general public. This research used qualitative methode with phenomenological approach. Data was collected by means of indepth interviews to the youth MSM attain the age of 17-23 old years in Jember District. Based on the results of research indicate that most of the MSM is difficult to communicate and interact socially in the family, school (college) and in the society. Therefore they were not being themself. When they did socialization in heterosexual society, they would follow the norms and rules that exist in society. Howefer when they did socialization in MSM community, they feel comfortable and could be himself. Because MSM always got isolated from society, they make community in order toreceive emotional support and getting acceptance (cohesive) from society. Howefer this condition can not solve their isolated feelings.Therefore the difficult problems getting proper information about reproductive health.Therefore, they become vulnerable to infection of Sexual Transmited Diseases and HIV/AIDS.